Cellular and humoral response to the fourth BNT162b2 mRNA COVID‐19 vaccine dose in patients with CLL. (23rd October 2022) - Benjamini, Ohad; Gershon, Rotem; Bar‐Haim, Erez; Lustig, Yaniv; Cohen, Hila; Doolman, Ram; Kedmi, Meirav; Ribakovsky, Elena; Kneller, Abraham; Hod, Tammy; Erez, Noam; Levy, Itzhak; et al.
Abstract: We assessed the humoral and cellular response to the fourth BNT162b2 mRNA COVID‐19 vaccine dose in patients with CLL. A total of 67 patients with CLL and 85 age matched controls tested for serologic response and pseudo‐neutralization assay. We also tested the functional T‐cell response by interferon gamma (IFNγ) to spike protein in 26 patients. Two weeks after the fourth vaccine antibody serologic response was evident in 37 (55.2%) patients with CLL, 20 /22 (91%) of treatment naïve, and 9/32 (28%) patients with ongoing therapy, compared with 100% serologic response in age matched controls. The antibody titer increased by 10‐fold in patients with CLL, however, still 88‐folds lower than age matched controls. Predictors of better chances of post fourth vaccination serologic response were previous positive serologies after second, third, and pre‐fourth vaccination, neutralizing assay, and treatment naïve patients. T‐cell response improved from 42.3% before the fourth vaccine to 84.6% 2 weeks afterwards. During the time period of 3 months after the fourth vaccination, 14 patients (21%) developed COVID‐19 infection, all recovered uneventfully. Our data demonstrate that fourth SARS‐CoV‐2 vaccination improves serologic response in patients with CLL to a lesser extent than healthy controls and induces functional T‐cell response.